2012
DOI: 10.1111/j.1365-2850.2012.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the potential outcomes of integrating emotionally competent behaviours into the care of psychiatric patients?

Abstract: This descriptive study explored the concept of emotional competence in inpatient psychiatric nurse's daily interactions. Psychiatric registered nurses were asked to identify interactions of emotional competence they experienced on the nursing unit. Content analysis revealed deficits in self-awareness, mood management and managing relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…That study with British psychiatric patients revealed that they complained of some nursing professionals that disrespected them, suggesting that these professionals worked in psychiatry only for the money, not because they liked what they did (Doas, 2013). The Australian nurses believed that so there is quality in nursing care in mental health services nursing professionals should enjoy their job and have a genuine interest in helping others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study with British psychiatric patients revealed that they complained of some nursing professionals that disrespected them, suggesting that these professionals worked in psychiatry only for the money, not because they liked what they did (Doas, 2013). The Australian nurses believed that so there is quality in nursing care in mental health services nursing professionals should enjoy their job and have a genuine interest in helping others.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation with 54 nursing professionals from psychiatric inpatient units in the United States identified that they had trouble interacting with patients when exposed to stressful situations (Doas, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A literature review reveals a gap in knowledge as few research studies, which were found, focused on exploring the components of emotional competence in nursing (Doas, ; Wilson & Carryer, ). In the field of nursing education, views of clinical educators of nursing education in New Zealand were explored, and revealed that individual and social skills were among the features of emotional competence (Wilson & Carryer, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of nursing education, views of clinical educators of nursing education in New Zealand were explored, and revealed that individual and social skills were among the features of emotional competence (Wilson & Carryer, ). Similarly, Doas () reviewed daily interactions of psychiatric nurses in Western Pennsylvania and found the concept of emotional competence to represent self‐awareness, mood management and managing relationships. No further studies were found in line with the main objective of this study; that is, explaining the characteristics of emotional competence for gerontological nurses in hospital settings in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…[6] EI competencies are essential components of professional nursing practice and include the ability to demonstrate empathy and self-awareness, along with motivating others, and demonstrating excellent interpersonal skills. [7] EI competencies are also crucial for nurses in managing emotions while working with multidisciplinary teams needed to advance clinical practice and improve client outcomes. [8]…”
Section: Introductionmentioning
confidence: 99%